MEMORY ENHANCING EFFECTS OF FICUS CARICA LEAVES IN HEXANE EXTRACT ON INTEROCEPTIVE BEHAVIORAL MODELS. - VASUNDHARA, SAXENA; HAFSA, AHMAD; RAJIV, GUPTA (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Abstract: Objective: Ficus carica Linn. (Moraceae) commonly known as the fig plant, a native of Carica in Asia is grown in nearly all tropical and sub-tropical countries. Phytochemical screening of the hexane extract confirmed the presence of flavonoids (quercetin) which have been associated with C.N.S. effects and also claimed to be the responsible C.N.S. active moiety, in recent studies. Hence it was thought worthy to investigate the cognitive effects of hexane extract of Ficus carica leaves, in normal and memory deficit mice using Y-maze and rectangular maze models (interoceptive behavioral models). Method: Hexane extracts of leaves of Ficus carica (dosed at 100 and 200mg/kg each) were administered to adult Swiss albino Wistar mice and the acquisition, retention and retrieval of spatial recognition memory was determined, by using Y-maze and rectangular maze models (interoceptive behavioral models). Bacopa monniera extract was used as the standard drug while scopolamine hydrobromide as the amnestic agent. Results: The higher doses of the plant extract, exhibited a more promising nootropic potential. Maximum response was observed in the 200mg/kg dose of extract, which closely approximated the results for the standard drug Brahmi. The higher dose elicited greater responses in both the models studied and where comparable to that achieved with the standard drug. Conclusion: The hexane extract of Ficus carica afforded mild memory enhancing effects, the higher dose evoking pronounced alteration of behavior and better learning assessments. Keywords: Ficus carica, Anjeer, cognition, H.P.T.L.C., Rectangular maze